Treatment of high risk Sertoli–Leydig cell tumors of the ovary using a gonadotropin releasing hormone (GnRH) analog1. Issue 6 (28th November 2012) - Lashkari, Harsha Prasada; Nash, Ruth; Albanese, Assunta; Okoye, Bruce; Millar, Robert; Pritchard‐Jones, Kathy
Abstract Sertoli–Leydig cell tumors are rare ovarian neoplasms. We report two unusual cases with bilateral SLCTs suggesting evidence of genetic predisposition and at high risk of recurrence. To reduce this risk, we exploited the use of GnRH analog to lower gondadotropin and potentially directly inhibit the tumors through expressed GnRH receptors. We used it as maintenance antitumor therapy for 2 years after completion of chemotherapy, to cover the period of risk for recurrence. Both patients remain in complete remission at >2 years after completing leuprorelin therapy. Of note, both patients carry DICER1 mutations, frequently found in pleuropulmonary blastoma syndrome. Pediatr Blood Cancer 2013; 60: E16–E18. © 2012 Wiley Periodicals, Inc.